(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This paper explores the paradigmatic relations of monosyllabic words in the French language, emphasizing their phonetic, lexical, morphological, and grammatical dimensions. Despite their brevity, monosyllables represent a highly dynamic and multifunctional element of the linguistic system. It also highlights their role in grammatical organization through prepositions and pronouns, as well as their contribution to phonetic contrasts and stylistic effects in literature. Furthermore, the paper demonstrates that monosyllables play an essential role in maintaining linguistic economy, rhythmic harmony, and semantic precision in French. By analyzing their associative relations, this study reveals the cognitive and structural significance of monosyllabic paradigms in shaping the expressiveness and balance of the French linguistic system.